2021
DOI: 10.3390/ijms23010064
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0000190 Facilitates the Tumorigenesis and Immune Evasion by Upregulating the Expression of Soluble PD-L1 in Non-Small-Cell Lung Cancer

Abstract: Lung cancer is the leading cause of death from cancer in Taiwan and throughout the world. Immunotherapy has revealed promising and significant efficacy in NSCLC, through immune checkpoint inhibition by blocking programmed cell death protein (PD)-1/PD-1 ligand (PD-L1) signaling pathway to restore patients’ T-cell immunity. One novel type of long, non-coding RNAs, circular RNAs (circRNAs), are endogenous, stable, and widely expressed in tissues, saliva, blood, urine, and exosomes. Our previous results revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Recent research has reported that circRNAs could act as ceRNAs to modulate PD‐L1 expression, thereby regulating tumor immune escape in many tumors 164 . For instance, hsa_circ_0000190 promoted tumor immune evasion by boosting sPD‐L1 expression in non‐small‐cell lung cancer 165 . Researchers have proved that the inhabitation of IDO, CTLA‐4, and PD‐L1 interacted with increased Treg‐associated long‐term survival in gliomas 166 .…”
Section: Circrna and Gliomamentioning
confidence: 99%
“…Recent research has reported that circRNAs could act as ceRNAs to modulate PD‐L1 expression, thereby regulating tumor immune escape in many tumors 164 . For instance, hsa_circ_0000190 promoted tumor immune evasion by boosting sPD‐L1 expression in non‐small‐cell lung cancer 165 . Researchers have proved that the inhabitation of IDO, CTLA‐4, and PD‐L1 interacted with increased Treg‐associated long‐term survival in gliomas 166 .…”
Section: Circrna and Gliomamentioning
confidence: 99%
“…Hsa_circ_0000190 enhances PD-L1 mRNA-mediated expression of soluble PD-L1 and promotes non-small cell lung carcinogenesis and immune evasion [ 86 ]. In addition, HasCircRNA-002178 is capable of enhancing PD-L1 expression by inducing T cell exhaustion via sponging miR-34 in LUAD cells [ 87 ].…”
Section: Lncrna and Circrnamentioning
confidence: 99%
“…MLL1 ↑PC [134] NRF2 ↑HCC [22] ATF3 ↑melanoma and NSCLC [55] Epigenetic regulation of PD-L1 DNA methylation ↓melanoma [62,64], leukemia [39] Histone modification ↓BC and B cell lymphomas [53,185], lung cancer [66] MicroRNAs shown in Table 1 N6-methyladenosine ↑OSCC [90], ↑BC [91] LncRNA and circRNA HOTTIP, SNHG12, EMX2OS-↑OC[76, 77, 81] SNHG20-↑esophagus cancer [78] CASC11-↑HCC [80] SNHG14-↑DLBCL [79] NUTM2A-AS1-↑GC [82] Hoxa-AS2-↑nasopharyngeal carcinoma [83] IFITM4P-↑OSCC [84] LncMX1-215-↓HNSCC [85] Hsa_circ_0000190-↑NSCLC [186] HasCircRNA-002178-↑ LUAD [87] CDR1-AS-↑CC [88] PD-L1 regulation at the protein level Ubiquitination ↓ BC [97], NSCLC [98], CC [99], colon cancer [100], melanoma [101,102,106], lung cancer [101], esophageal squamous cell carcinoma [105] Glycosylation ↑AML [108], TNBC [109,111], colon cancer [110], prostate cancer [111], glioma [112] Phosphorylation ↓ BC [114,116], HCC [115] Acetylation ↓ multiple cancers [117] Palmitoylation ↑ BC and colon cancer [118,…”
Section: Regulators Of Pd-l1 Cancer Typementioning
confidence: 99%
“…Multiple types of circular RNAs (circRNAs), for instance, hsa_circ_0000190 [ 236 ], hsa_circ_0079587 [ 237 ], circFGFR1 [ 238 ], circUSP7 [ 239 ], etc., have been found to be associated with promoting tumor progression, metastasis, immune evasion, and immunotherapy resistance [ 235 ]. These circRNAs provoke resistance to anti-PD-1 therapy by upregulating PD-L1 expression, targeting CXCR4, and inhibiting the infiltration of CD8+ T cells, which supports the necessity of targeting circRNAs to resensitize tumor cells to immunotherapy.…”
Section: Mechanism Of Immunotherapeutic Resistance and Overcoming Str...mentioning
confidence: 99%